Correlation between educators understanding and applying of role play activities for preschoolers language, social and emotion development - Xichun, Huang (2023)
This study aims to determine the relationship between educators' understanding and applying of role play activities for preschoolers' language, social, and emotion development. A quantitative study was used to collect questionnaires from preschool educators in Chaozhou, Guangdong Province, China, who teach preschoolers aged five to six years old. A total of 352 educators (Private Urban N=110, Private Rural N=73, Public Urban N=101, Public Rural N=68) were chosen as research samples using stratified random sampling. The online platform Questionnaire Star is used for questionnaire distribution, which has been validated by experts and pilot studies. Inferential statistical analyses, such as correlation and regression models, are used to interpret the findings. Results showed that educators' understanding and applying of role play have a positive effect on preschoolers' language development (r=0.31, p<0.00), social development (r=0.31, p<0.00), and emotion development (r=0.30, p<0.00). However, neither teaching experience nor types of preschools have a significant effect. Educators conduct little role play sessions in teaching activities, and costumes, props, and scripts are less used in role play activities. In conclusion, this study enriches the educational connotation of role play activities, comprehensively studies preschoolers' language, social, and emotion development, and further innovates and expands the theoretical research methods of preschoolers' development. Simultaneously, it provides a more scientific foundation for front-line educators and preschools to implement role play activities suitably.